La cartografía como base fundamental para el análisis del Urbanismo Maya. Cuestiones metodológicas - Peiró Vitoria, Andrea (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The urban form and composition of Maya settlements have generated many discussions and have been the subject of a substantial number of research projects. However, most of these studies have an historical and anthropological perspective rather than an approach from the disciplines of urban planning and architecture. After participating in the La Blanca Project (in Petén, Guatemala), and analyzing the interesting urban structure of this archaeological site, the idea emerged of conducting a comparative study of urban settlements in different areas of the Maya lowlands. The heterogeneity of cartography is one of the main difficulties we found for this research. Therefore, the creation of a homogeneous cartographical database, will be the key to adequately perform the subsequent studies of urban planning. The article will be available as a PDF in the near future.